Digital-Based HR Strategy and Its Role in Building an Adaptive Work Culture at PT Taspen - Yulisa Andriany; Setia Pramudya; Muhammad Farhan Ramadhan; Asheva Azahra; Satriadi Satriadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Various aspects of business, including human resource management (HR). Digital-based HR strategies are an urgent need for organizations to remain competitive and adaptive to change. This study aims to analyze the digital-based HR strategy implemented at PT Taspen Tanjungpinang and its role in building an adaptive work culture. Using a qualitative approach, data were collected through interviews and observations. The results of the study indicate that the implementation of technologies such as HRIS, e-learning, and digital communication platforms has increased the efficiency and effectiveness of HR management. The main challenges include employee adaptation to new technologies and budget constraints. However, adequate management support, training, and infrastructure are supporting factors for successful implementation. This study contributes to the development of digital-based HR strategies in other companies.